Analisis implementasi manajemen strategi dalam meningkatkan daya saing bank syariah di era digitalisasi keuangan - Rahman, Augie Ryan (Maliki Interdisciplinary Journal, 2025)
Digital technology is advancing rapidly and constantly giving rise to new generations that create superior innovations and help make work and activities more efficient and practical. This technological development has also changed several instruments in the financial world, especially in the banking sector, particularly Islamic banking institutions, in line with the theme of this article. With digitalization, there is fierce competition between Islamic banks and financial institutions that are no less competitive in the field of fintech. The purpose of this article is to analyze the implementation or application of strategic management applied by Islamic banks to increase competitiveness in this era of financial digitalization.